The powers and functions of the Pardons Board in Malaysia - a review / Norchaya Hj. Talib - Norchaya , Hj. Talib (1989)
Once a person is sentenced to death by the Supreme Court or a death sentence is affirmed by the Supreme Court, he will definitely be statement reflects the views of many hanged'people. This is because all legal channels of appeal have been exhausted. This is in fact untrue. The prisoner has yet another avenue of appeal - to the Pardons Board.